2001
DOI: 10.1093/milmed/166.8.671
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Behavior in Combat Veterans with Post-Traumatic Stress Disorder

Abstract: The incidence of aggression and violent behavior in combat veterans varies and can be observed with regard to the presence or absence of post-traumatic stress disorder (PTSD). Significantly greater occurrence of aggression was observed in combat veterans with PTSD compared with those without PTSD. There are various types of aggressive behavior that frequently are combined. Autoaggressive (suicidal) and heteroaggressive (interpersonal violence) behaviors predominate, with dominating verbal aggression and impuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 0 publications
3
52
1
1
Order By: Relevance
“…Consistent with other veteran studies, PTSD elevated risk of both domestic and interpersonal aggression (Begic & Jokic-Begic, 2001;Taft et al, 2005). The current study extends these findings by identifying PTSD as an independent risk factor for violent behavior in a psychiatric veteran sample with SMI.…”
Section: O N C L U S I O Nsupporting
confidence: 89%
“…Consistent with other veteran studies, PTSD elevated risk of both domestic and interpersonal aggression (Begic & Jokic-Begic, 2001;Taft et al, 2005). The current study extends these findings by identifying PTSD as an independent risk factor for violent behavior in a psychiatric veteran sample with SMI.…”
Section: O N C L U S I O Nsupporting
confidence: 89%
“…Forty percent of the 10 patients who had a diagnosis of both dementia and PTSD were aggressive, which was similar to the 41% incidence of aggression in the 205 patients who had dementia without a comorbid diagnosis of PTSD. These findings are inconsistent with data from previous researchers (Kulka et al, 1990;Lasko et al, 1994;Beckman et al, 1997;McFall et al, 1999;Begic and Jokic-Begic, 2001;Taft et al, 2007a;Taft et al, 2007aTaft et al, , 2007b. Some studies suggest that increased severity of PTSD symptoms is associated with an increased risk of aggression (Byrne and Riggs, 1996;O'Donnell et al, 2006).…”
Section: Discussioncontrasting
confidence: 71%
“…Many studies addressing consequences of traumatic experiences in war veterans found increased impulsive aggression towards intimate partners (Byrne & Riggs, 1996) and unknown persons (e.g., Begic & Jokic-Begic, 2001;Silva et al, 2001). Similarly, high rates of traumatic experiences were found in a sample of juvenile delinquents (Abram et al, 1994).…”
Section: Violence Breeds Violencementioning
confidence: 98%